Exclusion mapping of chromosomal regions which cross hybridise to FSHD1A associated markers in FSHD1B. Issue 10 (October 1995) - Gilbert, J R; Speer, M C; Stajich, J; Clancy, R; Lewis, K; Qiu, H; Yamaoka, L; Kumar, A; Vance, J; Stewart, C; Rozear, M; Roses, A D; et al.
Abstract : Facioscapulohumeral muscular dystrophy (FHSD) is a genetically heterogeneous, autosomal dominant primary disease of muscle. The predominant form of FSHD, which has been designated FSHD1A, has been localised to the 4q34 region of human chromosome 4. The disease locus (loci) for the remaining FSHD families, which are not linked to chromosome 4 and have been designated FSHD1B, has not yet been identified. The D4F104S1 marker which detects copies of a 3·2 kb tandem repeat (D4Z4) which contains several types of repetitive sequences, including Hox gene-like elements, has been shown to be closely linked to the chromosome 4 FHSD disease locus. The loss of an integral number of the 3·2 kb tandem repeats has been associated with FSHD1A. When hybridised to chromosomal spreads these sequences cross hybridise with heterochromatin on acrocentric chromosomes and specific areas of human chromosomes 1, 3, and 10. Potentially these specific regions of cross hybridisation may be linked to FSHD1B. To examine this possiblity we have carried out linkage studies in our largest FSHD1B family. In this paper we exclude these areas of specific cross hybridisation as disease loci for FSHD1B.